ANALISIS PROSES PRODUKSI DAN PENGIRIMAN AIR MINUM DALAM KEMASAN (AMDK) NGROWO AE PDAM TIRTA TAMAN SARI KOTA MADIUN - Meisha Farah Widyaningrum; Sonja Andarini (CV SWA Anugerah, 2025)
Merdeka Belajar Kampus Merdeka (MBKM) is one way to improve the quality of higher education by connecting the theories learned in college with the practices that exist in the industrial world. The internship activities carried out at the company at the Ngrowo AE Bottled Drinking Water (AMDK) production unit aim to provide students with direct experience regarding the operations of the AMDK industry, both from a managerial and technical production perspective. In this service, students have the opportunity to interact with various divisions in the company, from production, quality control, distribution, to marketing. It is hoped that this internship activity will not only improve student skills, but also make a real contribution to the progress of the Ngrowo AE AMDK industry.